Advance in Numerical Simulation Research of Marine Methane Processes - Xu, Sinan; Sun, Zhilei; Geng, Wei; Cao, Hong; Zhang, Xilin; Zhai, Bin; Wu, Zijun (Frontiers in Earth Science, 2022)
Understanding the modern marine methane processes, which can profoundly affect global climate and have far-reaching impacts on human living environments, is critical for research on the global carbon cycle. Thus, modeling of marine methane processes has attracted increasing attention due to models can accurately simulate and predict the environmental effects of methane on marine and atmospheric ecosystems. In this study, we review the applications of modeling works to marine methane processes, including methanogenesis in sediments, transport and reaction of methane in sediments and seawater, and marine methane emissions to the atmosphere. Compiled a large database of global methanogenesis rates and methane fluxes to the sulfate-methane transition zone, we estimate that the global methanogenesis budget in marine sediments is ~0.87 Tmol yr-1 and global sedimentary dissolved inorganic carbon produced by anaerobic oxidation of methane is ~8.9 Tmol yr-1. In addition, although anaerobic oxidation of methane in sediments and aerobic oxidation of methane in seawater act as primary filters to prevent methane leakage from sediments to the hydrosphere as well as the atmosphere, large masses of methane in extreme seafloor environments (e.g., mud volcanic eruptions and hydrate leakage) can still escape microbial oxidation and leakage to seawater or the atmosphere. There is still a lack of models that simulate methane in these extreme marine environments. Therefore, more modeling works are needed to assess the efficiency of marine ecosystems, including sediments and hydrosphere, in filtering methane in the event of large-scale methane leakage from the seafloor. This study provides an interdisciplinary view of methane processes in marine systems and helps identify future directions in the modeling of methane processes in marine system.